2023
DOI: 10.3390/biomedicines11051426
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell in Pancreatic Islet Transplantation

Serena Barachini,
Letizia Biso,
Shivakumar Kolachalam
et al.

Abstract: Pancreatic islet transplantation is a therapeutic option for achieving physiologic regulation of plasma glucose in Type 1 diabetic patients. At the same time, mesenchymal stem cells (MSCs) have demonstrated their potential in controlling graft rejection, the most fearsome complication in organ/tissue transplantation. MSCs can interact with innate and adaptive immune system cells either through direct cell-cell contact or through their secretome including exosomes. In this review, we discuss current findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…By far, the most prevalent source of MSCs in clinical trials is adult bone marrow, followed by adipose tissue and puerperal discards such as umbilical cord tissue and placental cells ( 80 ). In islet transplantation, MSCs can promote the polarization of mononuclear cells/macrophages to the M2 phenotype by secreting exosomes and cytokines including Indoleamine 2,3-dioxygenase (IDO), IL-4 and IL-10 ( 81 ), while inhibiting their differentiation to the M1 phenotype, reducing the production of IL-12 and blocking the maturation of dendritic cells; the ability of immature dendritic cells to present antigen will be diminished and ultimately weaken T-cell function, thus improving the survival rate of the transplanted islet ( 82 ). At present, the MSC research directions are mainly the selection of subgroups under different types and states and MSC engineering.…”
Section: Advances In Macrophage Studies In Islet Transplantationmentioning
confidence: 99%
“…By far, the most prevalent source of MSCs in clinical trials is adult bone marrow, followed by adipose tissue and puerperal discards such as umbilical cord tissue and placental cells ( 80 ). In islet transplantation, MSCs can promote the polarization of mononuclear cells/macrophages to the M2 phenotype by secreting exosomes and cytokines including Indoleamine 2,3-dioxygenase (IDO), IL-4 and IL-10 ( 81 ), while inhibiting their differentiation to the M1 phenotype, reducing the production of IL-12 and blocking the maturation of dendritic cells; the ability of immature dendritic cells to present antigen will be diminished and ultimately weaken T-cell function, thus improving the survival rate of the transplanted islet ( 82 ). At present, the MSC research directions are mainly the selection of subgroups under different types and states and MSC engineering.…”
Section: Advances In Macrophage Studies In Islet Transplantationmentioning
confidence: 99%
“…Pancreatic islet transplantation is a therapeutic option for treating Type I diabetes; however, acute islet loss is a significant complication of this procedure. Barachini et al reviewed various approaches using MSCs and MSC-EVs to create a more conducive immune microenvironment, aiming to reduce graft rejection and promote early vascularization to support graft survival [ 70 ]. Mrahleh et al reported that MSCs primed with IFN-γ and TNF-α exhibited an immunomodulatory effect on CD4 + and CD8 + T cells by producing tolerogenic dendritic cells, which inhibit antigen-specific T cell responses via induction T cell anergy [ 68 ].…”
Section: The Therapeutic Effects Of Ifn-γ-primed Mscs (The Relationsh...mentioning
confidence: 99%
“…However, some studies have suggested that the secretion of some trophic factors may play a role in this process. Although MSCs can be derived from different tissues in the body, most studies have indicated that the secretion of trophic factors, which promote islet revascularization, is responsible for improving metabolic graft function ( 8 ).…”
Section: Coculture and Cotransplantation Of Islets With Other Cellsmentioning
confidence: 99%
“…However, the shortage of pancreatic donors poses a significant obstacle for type 1 diabetes patients, as well as hindering the clinical application of islet transplantation. Recently cell-replacement therapies using functional insulin-producing pancreatic β cells generated from stem cell differentiation or transdifferentiation offer potential treatment options ( 8 ). However, these approaches still have several limitations compared to somatic islets derived from the same individual.…”
Section: Introductionmentioning
confidence: 99%